Передача со свободной обоймой - Ефременков Е. А. Егор Алексеевич; Шибинский К. Г. Константин Григорьевич; Мартынов А. К. Анатолий Кузьмич; Хлыст С. В. Сергей Васильевич; Иванов А. Г. Алексей Геннадьевич
опубл. 20.06.08, Бюл. № 17